Implementasi Metode Profile Matching Untuk Menentukan Posisi Ideal Pemain Sepakbola - Dwi Kurniawan Saputro; Nurchim Nurchim; Bondan Wahyu Pamekas (Universitas Islam Raden Rahmat, Malang, 2024)
Positioning in football is a factor that must be considered, because a game can run according to the tactics that have been made by the coach if the player's position is in accordance with his abilities and character.But in determining the position of the player requires sharp instincts and structured training so that the ideal position for each player is found. This research aims to provide assistance to coaches to determine the ideal position of players by creating asystem that can strengthen decisions and increase confidence in placing players in certain positions. This system uses the Profile Matching method, which uses the ideal value for each criterion and also the individual value of each player as a comparison.This research produces a system that shows the ideal position of the player with test results from 15 players resulting in a percentage of 80% match between the initial position and the recommended position.